Motivasi Kerja Guru Dalam Pengembangan Budaya Kerja Positif Di Sekolah Dasar Negeri Borong Kecamatan Manggala Kota Makassar - Andi Hidayati (Movere Journal, 2025)
This study aims to describe teachers' work motivation, actions taken to foster a positive work culture, as well as the supporting and inhibiting factors in developing a positive work culture at Borong Public Elementary School, Manggala District, Makassar City. This research employs a descriptive approach, with the principal and teachers as research subjects. Data were collected through interviews, observations, and documentation, and validated using source and technique triangulation. The results show that: (1) Teachers' work motivation is reflected in their enthusiasm for performing duties, responsibility in teaching and evaluating learning outcomes, interest in tasks, and efforts to develop competencies and value their profession; (2) Actions to build a positive work culture include enforcing discipline and responsibility, promoting collaboration, openness, and mutual respect among school members; (3) Supporting factors consist of internal aspects such as educational qualifications, teaching needs, and teacher welfare, as well as external aspects like work environment, school leadership, and institutional regulations. Inhibiting factors involve internal issues related to teacher quality and external challenges in interacting with students of diverse characteristics.